1993
DOI: 10.1109/20.281351
|View full text |Cite
|
Sign up to set email alerts
|

The gap recession reduced MIG head

Abstract: Abstruct--In order to reduce the decrease of head output level during running, the wear recession formed on a composite material and MIG heads with various ferrite crystallographic orientations was investigated. It was found that wear recess depends mainly on the wear rate iatio Gf materhls, and that the decrease in output level was in proportion to the spacing loss due to the formation of a level difference at the interface between the metal and the ferritr core. However the decrease measured using different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The probe (tapping-mode tip) is brought closer to the sample to establish intermittent contact with the surface. A simple model to describe PTR has been reported by Tsuchiya et al (1993). The removal rate of materials was calculated by assuming linear and arch-like behavior, with removal rate coefficients of k s and k m for the alumina and metal tips, respectively.…”
Section: Ptr Measurementsmentioning
confidence: 99%
“…The probe (tapping-mode tip) is brought closer to the sample to establish intermittent contact with the surface. A simple model to describe PTR has been reported by Tsuchiya et al (1993). The removal rate of materials was calculated by assuming linear and arch-like behavior, with removal rate coefficients of k s and k m for the alumina and metal tips, respectively.…”
Section: Ptr Measurementsmentioning
confidence: 99%
“…Previous studies showed that metal core recession depended on the relative wear rates of various head materials and the kind of tape being used in the tape drive (20,21). Experiments with an 8-mm camcorder which uses amorphous CoNbZr metal in gap (MIG) heads showed that metal core recession reached a stable value in about 15 h of streaming mode operation and that ME tape caused larger metal core recession than MP and BaFeO tapes (22).…”
Section: Introductionmentioning
confidence: 97%
“…PTR in sandwich heads is further complicated by differential wear of lamination layers within the soft magnetic sandwich, which may either be recessive or protrusive as compared to the soft magnetic material. Possible mechanisms for PTR have been modelled by Tsuchiya, Abe and Noro (1,2) and by Broese van Groenau et al (3). The former find PTR to be broadly independent of the form of the composite head (MIG, sandwich, etc.)…”
Section: Introductionmentioning
confidence: 98%
“…Of prime importance is the nature of the head±tape contact. Intimate contact is desired to minimize signal loss, as governed by equation (1). An air bearing is required to prevent catastrophic damage on repeated head±tape collision in the helical scan mode.…”
Section: Introductionmentioning
confidence: 99%